A high-throughput ratiometric method for imaging hypertrophic growth in cultured primary cardiac myocytes. (May 2019) - Loonat, Aminah A.; Curtis, M. Kate; Richards, Mark A.; Nunez-Alonso, Graciela; Michl, Johanna; Swietach, Pawel
Abstract: Maladaptive hypertrophy of cardiac myocytes increases the risk of heart failure. The underlying signaling can be triggered and interrogated in cultured neonatal ventricular myocytes (NRVMs) using sophisticated pharmacological and genetic techniques. However, the methods for quantifying cell growth are, by comparison, inadequate. The lack of quantitative, calibratable and computationally-inexpensive high-throughput technology has limited the scope for using cultured myocytes in large-scale analyses. We present a ratiometric method for quantifying the hypertrophic growth of cultured myocytes, compatible with high-throughput imaging platforms. Protein biomass was assayed from sulforhodamine B (SRB) fluorescence, and image analysis calculated the quotient of signal from extra-nuclear and nuclear regions. The former readout relates to hypertrophic growth, whereas the latter is a reference for correcting protein-independent (e.g. equipment-related) variables. This ratiometric measure, when normalized to the number of cells, provides a robust quantification of cellular hypertrophy. The method was tested by comparing the efficacy of various chemical agonists to evoke hypertrophy, and verified using independent assays (myocyte area, transcripts of markers). The method's high resolving power and wide dynamic range were confirmed by the ability to generate concentration-response curves, track the time-course of hypertrophic responses with fine temporal resolution, describe drug/agonist interactions, and screen for novel anti-hypertrophic agents. The method can be implemented as an end-point in protocols investigating hypertrophy, and is compatible with automated plate-reader platforms for generating high-throughput data, thereby reducing investigator-bias. Finally, the computationally-minimal workflow required for obtaining measurements makes the method simple to implement in most laboratories. Highlights: Maladaptive hypertrophy of myocytes can lead to heart failure. Common methods for tracking growth in cultured myocytes are inadequate. We design and test a method for tracking myocyte hypertrophy in vitro. The method provides a ratiometric index of growth for high throughput analyses. Using the method, we characterize further details of (anti)hypertrophic responses.